Association Between Early Oral β-Blocker Therapy and In-Hospital Outcomes in Patients With ST-Elevation Myocardial Infarction With Mild-Moderate Heart Failure: Findings From the CCC-ACS Project - Wang, Miao; Liu, Jing; Liu, Jun; Hao, Yongchen; Yang, Na; Liu, Tong; Smith, Sidney C.; Huo, Yong; Fonarow, Gregg C.; Ge, Junbo; Morgan, Louise; Ma, Changsheng; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: There are limited data available on the impact of early (within 24 hours of admission) β-blocker therapy on in-hospital outcomes of patients with ST-elevation myocardial infarction (STEMI) and mild-moderate acute heart failure. This study aimed to explore the association between early oral β-blocker therapy and in-hospital outcomes. Methods: Inpatients with STEMI and Killip class II or III heart failure from the Improving Care for Cardiovascular Disease in China project (n=10,239) were enrolled. The primary outcome was a combined endpoint composed of in-hospital all-cause mortality, successful cardiopulmonary resuscitation after cardiac arrest, and cardiogenic shock. Inverse-probability-of-treatment weighting, multivariate Cox regression, and propensity score matching were performed. Results: Early oral β-blocker therapy was administered to 56.5% of patients. The incidence of the combined endpoint events was significantly lower in patients with early therapy than in those without (2.7% vs. 5.1%, P<0.001). Inverse-probability-of-treatment weighting analysis demonstrated that early β-blocker therapy was associated with a low risk of combined endpoint events (HR=0.641, 95% CI: 0.486–0.844, P=0.002). Similar results were shown in multivariate Cox regression (HR=0.665, 95% CI: 0.496–0.894, P=0.007) and propensity score matching (HR=0.633, 95% CI: 0.453–0.884, P=0.007) analyses. A dose-response trend between the first-day β-blocker dosages and adverse outcomes was observed in a subset of participants with available data. No factor could modify the association of early treatment and the primary outcomes among the subgroups analyses. Conclusions: Based on nationwide Chinese data, early oral β-blocker therapy is independently associated with a lower risk of poor in-hospital outcome in patients with STEMI and Killip class II or III heart failure.